The impact of payoff, societal contribution and conviction to entrepreneurial intention among Chinese students in Universiti Utara Malaysia - Maosen, Sun (2015)
The purpose of this study is to analyze the influence of payoff, societal contribution, and conviction on entrepreneurial intention among Chinese university students based on the Theory of Planned Behavior. The current efforts by the government of China to increase interest in entrepreneurship among Chinese students in response to the growing challenges of poverty and unemployment have motivated the conduct of this study. The population of the study covers the Chinese students in Universiti Utara Malaysia. Using correlation analysis, this study has found that all variables (i.e. payoff, societal contribution, and conviction) are positively correlated to entrepreneurial intention. A more robust test by means of multiple regression, on the other hand, shows that among other variables, payoff positively and significantly influences entrepreneurial intention. This shows that payoff is the most attractive element for Chinese university students to engage in entrepreneurship. Thus, focus on payoff is crucial in order to promote greater interest for entrepreneurship among Chinese students